2010
DOI: 10.1302/0301-620x.92b9.24476
|View full text |Cite
|
Sign up to set email alerts
|

Photographic measurement of the inclination of the acetabular component in total hip replacement using the posterior approach

Abstract: The angle of inclination of the acetabular component in total hip replacement is a recognised contributing factor in dislocation and early wear. During non-navigated surgery, insertion of the acetabular component has traditionally been performed at an angle of 45 degrees relative to the sagittal plane as judged by the surgeon's eye, the operative inclination. Typically, the method used to assess inclination is the measurement made on the postoperative anteroposterior radiograph, the radiological inclination. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 22 publications
3
30
0
Order By: Relevance
“…Any undetected pelvic movement, particularly about the antero-posterior axis will affect the angle achieved using the new device (23). This movement may be due to rotation about the lumbar spine whilst lying in lateral decubitus as suggested in previous work from this unit (21). Di Gioia et al measured a range of pelvic movements in the lateral decubitus position intra-operatively.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Any undetected pelvic movement, particularly about the antero-posterior axis will affect the angle achieved using the new device (23). This movement may be due to rotation about the lumbar spine whilst lying in lateral decubitus as suggested in previous work from this unit (21). Di Gioia et al measured a range of pelvic movements in the lateral decubitus position intra-operatively.…”
Section: Discussionmentioning
confidence: 98%
“…The surgeon must be aware that operative is not the same as radiographic inclination. Hill et al (21) found, on average, radiographic inclination was 13° greater than operative inclination in the lateral decubitus position and advised surgeons to chose a maximum of 35° of operative inclination to avoid excessive radiographic inclination. This study aimed to minimise inter and intra-user variability when positioning the acetabular cup during THA with a low cost technique that did not add to the overall procedure time or increase the complexity of implantation but that also allowed the surgeon to chose and record what angle of inclination was selected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…31,32 Further, variability of patient positioning in the lateral decubitus restricts correct identification of the coronal plane. Supine patient positioning for THR with a stable pelvic position and the coronal plane positioned parallel to the operating table and the floor reduces these problems.…”
Section: Discussionmentioning
confidence: 99%
“…Hill et al 71. reported a 12.7° variation between implanted inclination angle and final position on radiographs despite careful implantation.…”
Section: How To Achieve Target Angular Positionmentioning
confidence: 99%